Novel truncating variant of MN1 penultimate exon identified in a Chinese patient with newly recognized MN1 C‐terminal truncation syndrome: Case report and literature review. Issue 1 (4th November 2021) - Zhao, Arman; Shu, Dandan; Zhang, Daxue; Yang, Bin; Hong, Liyi; Wang, Andi; Yao, Ruen; Wang, Jian; Lv, Haitao; Wang, Jian; Shen, Yiping; Wang, Hongying; et al.
Abstract: MN1 C‐terminal truncation (MCTT) syndrome is a newly recognized neurodevelopmental disorder due to heterozygous gain‐of‐function C‐terminal truncating mutations clustering in the last or penultimate exon of MN1 gene (MIM: 156100). Up to date, only 25 affected patients have been reported. Here, we report a 2‐year‐old Chinese girl with MCTT syndrome. The girl presented with the characteristic features of the syndrome, including global developmental delay (GDD), facial dysmorphism and hearing impairment. Notably, the patient did not have other frequently observed symptoms such as hypotonia, cranial or brain abnormalities, indicating variability of the phenotype of patients with MN1 C‐terminal truncating mutations. Trio whole‐exome sequencing revealed a novel de novo heterozygous nonsense variant in the extreme 3′ region of penultimate exon of MN1 (NM_002430.3: c.3743G > A, p.Trp1248*). This rare truncating variant was classified as pathogenic due to its predicted gain‐of‐function effect, given that the gain‐of‐function MN1 truncating variants producing C‐terminally truncated proteins have been confirmed to cause the recognizable syndrome. Additionally, a systematic review of previously reported MN1 variants including C‐terminal truncating variants and N‐terminal truncating variants shows that different location of MN1 truncating variants causes two distinct clinical subtypes. To our knowledge, this is the first reported case of MCTT syndrome caused by a novel MN1 C‐terminal truncating variant in a Chinese population, which enriched the mutation spectrum of MN1 gene and further supporting the association of the novel MCTT syndrome with MN1 C‐terminal truncating variants. Abstract : The first reported case of MCTT syndrome was caused by a novel MN1 C‐terminal truncating variant (NM_002430.3: c.3743G > A, p.Trp1248*) in a Chinese population, which enriched the mutation spectrum of MN1 gene and further supporting the association of the novel MCTT syndrome with MN1 C‐terminal truncating variants.